Application of wave equation theory to improve dynamic cone penetration test for shallow soil characterisation - Miguel Angel Benz Navarrete; Pierre Breul; Roland Gourvès (Journal of Rock Mechanics and Geotechnical Engineering, 2022)
Among the geotechnical in situ tests, the dynamic penetration test (DPT) is commonly used around the world. However, DPT remains a rough technique and provides only one failure parameter: blow count or cone resistance. This paper presents an improvement of the dynamic cone penetration test (DCPT) for soil characterisation based on the wave equation theory. Implemented on an instrumented lightweight dynamic penetrometer driving with variable energy, the main process of the test involves the separation and reconstruction of the waves propagating in the rods after each blow and provides a dynamic cone load-penetration (DCLT) curve. An analytical methodology is used to analyse this curve and to estimate additional strength and deformation parameters of the soil: dynamic and pseudo-static cone resistances, deformation modulus and wave velocity. Tests carried out in the laboratory on different specimens (wood, concrete, sand and clay) in an experimental sand pit and in the field demonstrated that the resulting DCLT curve is reproducible, sensitive and reliable to the test conditions (rod length, driving energy, etc.) as well as to the soil properties (nature, density, etc.). Obtained results also showed that the method based on shock polar analysis makes it possible to evaluate mechanical impedance and wave velocity of soils, as demonstrated by the comparisons with cone penetration test (CPT) and shear wave velocity measurements made in the field. This technique improves the method and interpretation of DPT and provides reliable data for shallow foundation design.